2020
DOI: 10.1590/0102-33062020abb0263
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the germination requirements for Cereus hildmannianus (Cactaceae), a potential new crop from southern and southeastern Brazil

Abstract: Cereus hildmannianus K. Schum is a columnar cactus native to South and Southeast Brazil. The cultivation of this species seems justifiable for several reasons: its fruits are spineless and edible; it is not threatened with extinction; it naturally occurs in Pampa and Atlantic Forest under non-xeric conditions that may be unsuitable for the cultivation of other tropical cacti; and the plants are pollinator-dependent and so should benefit from native pollinators. This study aimed to test seed germination of C. h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In a review of seed traits and germination in the Cactaceae, Barrios et al (2020) found that the majority of taxa demonstrate optimal germination between 25 and 30 C. This generalization largely holds within the genus Cereus , but some variation between species has been reported. At constant temperatures, maximum germination for C. hildmannianus was found at 20 and 25 C (Becker et al 2020), for Cereus hankeanus F.A.C. Weber ex K.…”
Section: Resultsmentioning
confidence: 99%
“…In a review of seed traits and germination in the Cactaceae, Barrios et al (2020) found that the majority of taxa demonstrate optimal germination between 25 and 30 C. This generalization largely holds within the genus Cereus , but some variation between species has been reported. At constant temperatures, maximum germination for C. hildmannianus was found at 20 and 25 C (Becker et al 2020), for Cereus hankeanus F.A.C. Weber ex K.…”
Section: Resultsmentioning
confidence: 99%
“…Cereus hildmannianus is a columnar arborescent cactus with nocturnal anthesis and depends entirely on the pollination of Sphingidae moths. It is a species with wide geographic distribution in Brazil, and the optimum germination temperature is 25ºC (Becker, Dal Ri, Singer, & Singer, 2020). In Campo Mourão outcrops, several individuals are associated with the edge or nucleation regions of the Nishida outcrop, where the soil is already deeper.…”
Section: Discussionmentioning
confidence: 99%
“…The flowers are long (up to 20 cm in length) and their coloration varies from white to clear pink [ 3 ] ( Figure 1 a–c). The fruits of this species are smooth, spineless, and edible [ 10 ]. In contrast, P. aculeata Mill.…”
Section: Methodsmentioning
confidence: 99%
“…and Pereskia aculeata Mill. Cereus hildmannianus is popularly known as “Tuna” and its edible, sweet, spineless fruits make them valuable for horticultural purposes [ 10 ]. A very similar species, Cereus peruvianus (Pfeiff.)…”
Section: Introductionmentioning
confidence: 99%